Loss of PKCθ, Bcl10, or Malt1 selectively impairs proliferation and NF-κB activation in the CD4(+) T cell subset - Kingeter, Lara M. (2008)
The cytosolic proteins PKCθ, Bcl10, and Malt1 play critical roles in T cell receptor (TCR) signaling to the transcription factor nuclear factor κB (NF-κB). Our data confirm that CD4(+) T cells from PKCθ, Bcl10 and Malt1 knock-out mice show severe impairment of proliferation in response to TCR stimulation. Unexpectedly, we find that knock-out CD8(+) T cells proliferate to a similar extent as wild-type cells in response to strong TCR signals, although a survival defect prevents their accumulation. Both CD4(+) and CD8(+) knock-out T cells express activation markers, including CD25, following TCR stimulation. Addition of exogenous interleukin-2 (IL-2) rescues survival of knock-out CD4(+) and CD8(+) T cells, but fails to overcome the proliferation defect of CD4(+) T cells. CD4(+) T cells from knock-out mice are extremely deficient in TCR-induced NF-κB activation, whereas NF-κB activation is only partially impaired in CD8(+) T cells. Overall, our results suggest that defects in TCR signaling through PKCθ, Bcl10 and Malt1 predominantly impair NF-κB activation and downstream functional responses of CD4(+) T cells. In contrast, CD8(+) T cells maintain substantial NF-κB signaling, implying the existence of a significant TCR-regulated NF-κB activation pathway in CD8(+) T cells that is independent of PKCθ, Bcl10 and Malt1.